An Extension of Generalized (𝜓,𝜑)-Weak Contractions - Tran Van An; Kieu Phuong Chi; Erdal Karapınar; Tran Duc Thanh (International Journal of Mathematics and Mathematical Sciences)
We prove a fixed-point theorem for a class of maps that satisfy generalized (𝜓,𝜑)-weak contractions depending on a given function. An example is given to illustrate our extensions.